المنهج التاريخي للدكتور حسين أمين وموارده - راضي، سالم جاسم; عمران، وفاء عبدالجبار (جامعة بغداد - كلية الآداب, 2021)
Dr. Hussein Amin is a historian, researcher, radio and television personality ... He is the historian who has not emerged from the silo of history for more than 60 years. He was born in the Bab al-Boub neighborhood near the great door in Baghdad in 1923, he studied in the primary safety and in the western middle school, And his colleagues in the formation of a national cultural association known as the Arab Youth after the death of King Ghazi (April 1939) . He graduated from the Central High School and entered the Teachers' Primary School in 1945, where he was appointed and then traveled to Alexandria, Egypt to complete his studies. He received his bachelor's, master's and doctoral degrees in 1960. He was the first Iraqi to receive a doctorate from Alexandria University in Islamic history. Jamal Abdul Nasser, Dr. Hussein Amin (the Iraqi Historical Society) founded and became its president since the beginning of the seventies of the last century, and was elected first Secretary General of the Union of Arab Historians. More than 650 radio interviews were presented in heritage and history issues. He also participated in many Iraqi, Arab and foreign historical conferences. He is a member of the Paris-based International Historical Society. It has had close links with many Arab and international cultural institutions.
الحمد لله الأول قبل كل شيء والأخر بعد فناء كل شيء والصلاة والسلام على خير الأنام البشير النذير السراج المنير الطهر الطاهر النبي الأمين محمد ذي الخلق العظيم والطرائق القويمة والصلاة والسلام على آل بيته الأطهار ومن والاه إلى يوم الدين. يعد الدكتور حسين أمين من المؤرخين الذين أضافوا إلى المكتبة العلمية والتاريخية الكم الكثير من المؤلفات والموضوعات المختلفة التي أتحفت المكتبة العراقية والعربية بكم كبير زاد على أكثر من 300 مؤلف في التاريخ الإسلامي والترجمة والتحقيق وهو بذلك استطاع أن يجمع ويولم بالثقافات التي دونت ولم تسلط الأضواء عليها، فكان الزاماً على طلبة الدراسات العليا الاقتداء برواد المدرسة التاريخية العراقية والاهتمام بتراثهم الفكري والعلمي ولاسيما من أفني عمره في دراسة التاريخ الإسلامي لأكثر من سبعة عقود، فأوجدوا خاصية لهذه المدرسة الحديثة في التقصي والبحث المستمر، وإيجاد أسلوب جديد يتناسب مع العصر الحديث. ومن بين هؤلاء الرواد الدكتور حسين أمين الذي كان يردد " أن تاريخنا لم يكتب بعد". وقوله: "سنعيد كتابه تاريخ الأمة بأسلوب علمي وموضوعي" وبرز في طرح الأفكار الحديثة لقراءته التاريخية بنظرة جديدة تختلف عمن سبقه في هذا المجال. وعلى هذا تأتى أهمية الموضوع كون الدكتور حسين أمين من بين النخبة التي نهضت بالمدرسة التاريخية الحديثة من خلال كتاباته، وتسليط الضوء على موضوعات لم تسلط عليها الأضواء، ومقتدياً ومستنيراً بأساتذته الكبار، أمثال الدكتور مصطفى جواد، والدكتور صالح أحمد العلي، وغيرهما.
Keywords: المنهج التاريخي -- البحث العلمي -- أمين، حسين -- الوثائق التاريخية